ANALISIS TERHADAP KERAGAMAN BATAS UMUR ANAK DITINJAU MENURUT PERATURAN PERUNDANG-UNDANGAN DAN PUTUSAN HAKIM DALAM PERKARA PERDATA DI PENGADILAN NEGERI. - Nurul Hikmah, Iman Jauhari, Syarifuddin Hasyim, (Jurnal Ilmu Hukum, 2015)
Abstract: Legal system in Indonesia, which regulates the maturity that is always associated with a particular action. Age limit diversity creates legal uncertainty, debate on the issue of maturity is still common. Adults in legal actions in Act 1 of 1974 on Marriage Article 47 paragraph (1) states that the child has not reached the age of 18 ( eighteen) years or have never hold a marriage is under the authority of his parents for not deprived of its power, while Law. 4 of 1979 concerning child welfare clause of Article 1 (2) states